The inhibition of HIV-1 activity by crude mucus and purified mucin (mucous glycoproteins) from saliva, breast milk and the cervical tract of normal subjects, HIV positive individuals and patients with HIV-AIDS - Habte, Habtom Haileselassie (Department of Surgery, 2014)
Includes bibliographical references (leaves 140-161).